The synergistic effects of phenyllactic acid and slightly acid electrolyzed water to effectively inactivate Klebsiella oxytoca planktonic and biofilm cells. (July 2021) - Liu, Fang; Tang, Chun; Wang, Debao; Sun, Zhilan; Du, Lihui; Wang, Daoying
Abstract: 3-Phenyllactic acid (PLA) and slightly acid electrolyzed water (SAEW) are effective antimicrobial agents with broad-spectrum activity. The combined effects of PLA and SAEW on the inactivation of Klebsiella oxytoca planktonic and biofilm cells were evaluated in this study. The K. oxytoca K6 planktonic and biofilm cells were treated with PLA (0.5%, 1% and 2%), SAEW (30 and 60 mg/L), 0.5% PLA plus 30 mg/L SAEW, and 1% PLA plus 30 mg/L SAEW for 5, 10, 20, 30, and 60 min. The planktonic and biofilm cell assays showed that 2% PLA was more effective for the inactivation of K. oxytoca planktonic and biofilm cells than the other agents, and the combination of PLA and SAEW was more effective than the single agents at the same concentrations. Confocal laser scanning microscopy and ATP leakage analysis showed that the combined treatment of PLA and SAEW at different concentrations destroyed the cell membrane integrity of K. oxytoca planktonic and biofilm cells and caused ATP leakage at different levels. Scanning electron microscopy (SEM) assays showed that the morphologies of K. oxytoca planktonic and biofilm cells changed after treatment with the antibacterial agents at different levels. The cells were seriously damaged after treatment with 1% PLA and 30 mg/L SAEW for 60 min. The biofilm polysaccharide detection assays showed that SAEW-containing antibacterial agents were effective for disrupting the biofilm extracellular polymeric matrix, as shown in SEM images. The combination of PLA and SAEW effectively inactivated K. oxytoca planktonic and biofilm cells by damaging the cell membrane and disrupting the biofilm matrix. Highlights: PLA and SAEW showed synergistic effect in inactivating K. oxytoca planktonic and biofilm cells. The integrity of cell membrane of planktonic and biofilm cells was destroyed. The extracellular polymeric matrix in biofilm was effectively disrupted by SAEW-containing antibacterial agents.